The German Version of the Manchester Triage System and its quality criteria--first assessment of validity and reliability. - Ingo Gräff; Bernd Goldschmidt; Procula Glien; Manuela Bogdanow; Rolf Fimmers; Andreas Hoeft; Se-Chan Kim; Daniel Grigutsch (PLoS ONE)
Background The German Version of the Manchester Triage System (MTS) has found widespread use in EDs across German-speaking Europe. Studies about the quality criteria validity and reliability of the MTS currently only exist for the English-language version. Most importantly, the content of the German version differs from the English version with respect to presentation diagrams and change indicators, which have a significant impact on the category assigned. This investigation offers a preliminary assessment in terms of validity and inter-rater reliability of the German MTS. Methods Construct validity of assigned MTS level was assessed based on comparisons to hospitalization (general / intensive care), mortality, ED and hospital length of stay, level of prehospital care and number of invasive diagnostics. A sample of 45,469 patients was used. Inter-rater agreement between an expert and triage nurses (reliability) was calculated separately for a subset group of 167 emergency patients. Results For general hospital admission the area under the curve (AUC) of the receiver operating characteristic was 0.749; for admission to ICU it was 0.871. An examination of MTS-level and number of deceased patients showed that the higher the priority derived from MTS, the higher the number of deaths (p<0.0001 / χ² Test). There was a substantial difference in the 30-day survival among the 5 MTS categories (p<0.0001 / log-rank test).The AUC for the predict 30-day mortality was 0.613. Categories orange and red had the highest numbers of heart catheter and endoscopy. Category red and orange were mostly accompanied by an emergency physician, whereas categories blue and green were walk-in patients. Inter-rater agreement between expert triage nurses was almost perfect (κ = 0.954). Conclusion The German version of the MTS is a reliable and valid instrument for a first assessment of emergency patients in the emergency department.